2020
DOI: 10.1073/pnas.2000188117
|View full text |Cite
|
Sign up to set email alerts
|

Quantum spin-liquid states in an organic magnetic layer and molecular rotor hybrid

Abstract: The exotic properties of quantum spin liquids (QSLs) have continually been of interest since Anderson’s 1973 ground-breaking idea. Geometrical frustration, quantum fluctuations, and low dimensionality are the most often evoked material’s characteristics that favor the long-range fluctuating spin state without freezing into an ordered magnet or a spin glass at low temperatures. Among the few known QSL candidates, organic crystals have the advantage of having rich chemistry capable of finely tuning their microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…In a new class of hybrid organic crystals [EDT-TTF-CONH 2 ] 2 [BABCO] Szirmai et al [594] suggested that a quantum-spin-liquid state is introduced not by frustration -which is only t : t : t = 1.00 : 0.75 : 060 -but mainly by disorder that originates in the molecular rotor BABCO − [595,596]. Despite the rather strong coupling of J ≈ 314 K, the compound does not show indications of a magnetic phase transition down to 20 mK.…”
Section: Randomnessmentioning
confidence: 99%
“…In a new class of hybrid organic crystals [EDT-TTF-CONH 2 ] 2 [BABCO] Szirmai et al [594] suggested that a quantum-spin-liquid state is introduced not by frustration -which is only t : t : t = 1.00 : 0.75 : 060 -but mainly by disorder that originates in the molecular rotor BABCO − [595,596]. Despite the rather strong coupling of J ≈ 314 K, the compound does not show indications of a magnetic phase transition down to 20 mK.…”
Section: Randomnessmentioning
confidence: 99%
“…Because of the extended triangular arrangement of spin- 1 / 2 centers in these 2DCPs, such AFM coupling would lead to magnetic frustration, due to the impossibility of having all spin centers antiferromagnetically coupled with their nearest neighbors. Such a frustrated situation makes our proposed 2DCPs purely organic candidates to host unusual magnetically ordered states and, potentially, QSL-based states. , We note that our strategy could also be applicable to other 2DCPs based on open-shell organic molecular building blocks e.g., triangulenes . Considering different chemical functionalizations of the aryl rings for N-mv-2DCP, we find that the strength of such (frustrated) AFM interactions may be tuned from ca.…”
Section: Discussionmentioning
confidence: 90%
“…Such a frustrated situation makes our proposed 2DCPs purely organic candidates to host unusual magnetically ordered states 36 and, potentially, QSL-based states. [56][57][58]75 We note that our strategy could also be applicable to other 2DCPs based on open-shell organic molecular building blocks e.g., triangulenes. 76 Considering different chemical functionalizations of the aryl rings for N-mv-2DCP, we find that the strength of such (frustrated) AFM interactions may be tuned from ca.…”
Section: ■ Conclusionmentioning
confidence: 97%
“…Its possibility of mobile spinons was proposed, and the proximity to Mott boundary indicated that a spinon‐deconfined chargon‐glass insulator might dominate the QSL state. Furthermore, disorder generated by randomly frozen BABCO‐rotors induced the QSL state in EDT‐TTF‐CONH 2 +2 BABCO−(EDT‐BCO), where the cations carrying S = 1/2 spins formed a triangular lattice with spatial anisotropy 212 . The DFT calculation suggested that the anisotropy was not strong enough for dimensionality reduction, and this less frustrating system was expected to show chiral or collinear LRO states.…”
Section: Quantum Spin Liquidsmentioning
confidence: 99%
“…Furthermore, disorder generated by randomly frozen BABCO-rotors induced the QSL state in EDT-TTF-CONH 2 +2 BABCO−(EDT-BCO), where the cations carrying S = 1/2 spins formed a triangular lattice with spatial anisotropy. 212 The DFT calculation suggested that the anisotropy was not strong enough for dimensionality reduction, and this less frustrating system was expected to show chiral or collinear LRO states. However, tests including ESR, NMR, and µSR could not provide evidence for the formation of magnetic order but supported the appearance of a QSL state.…”
Section: Charge Transfer Saltsmentioning
confidence: 99%